Asian Economic Integration in an Era of Global Uncertainty (PAFTAD) - Armstrong, Shiro; Westland, Tom (ANU Press, 2018)
"The Pacific Trade and Development (PAFTAD) conference series has been at the forefront of analysing challenges facing the economies of East Asia and the Pacific since its first meeting in Tokyo in January 1968. The 38th PAFTAD conference met at a key time to consider international economic integration. Earlier in the year, the people of the United Kingdom voted to leave the European Union and the United States elected Donald Trump as their next president on the back of an inward-looking 'America First' promise. Brexit and President Trump represent a growing, and worrying, trend towards protectionism in the North Atlantic countries that have led the process of globalisation since the end of the Second World War. The chapters in the volume describe the state of play in Asian economic integration but, more importantly, look forward to the region's future, and the role it might play in defending the global system that has underwritten its historic rise. Asia has the potential to stand as a bulwark against the dual threats of North Atlantic protectionism and slowing trade growth, but collective leadership will be needed regionally and difficult domestic reforms will be required in each country."